Abusive supervision and the knowledge worker productivity: the mediating role of knowledge management processes. Issue 10 (18th May 2021) - Ahmed, Quba; Sumbal, Muhammad Saleem; Akhtar, Muhammad Naseer; Tariq, Hussain
Abstract : Purpose: Drawing upon the theoretical underpinning of knowledge worker productivity, this study aims to examine the relationship between abusive supervision and knowledge management (KM) process (creation, application and sharing of knowledge) and its impact on the knowledge worker productivity in knowledge-intensive organizations. Design/methodology/approach: Hypothesis were tested through PROCESS Macro in IBM SPSS v.26 on a sample of 204 employees working in banking sector of Pakistan. Confirmatory factor analysis was conducted to test the model fitness through AMOS v. 26. Findings: The results showed that the relationship between abusive supervision and KM process (creation, application and sharing of knowledge) is negative and highly significant, i.e. greater the abusive supervision in the banking sector, the lower is the engagement in KM processes. Furthermore, there is a positive and highly significant relationship between the KM process and knowledge worker productivity. Finally, the study indicates the negative impact of abusive supervision on the knowledge worker productivity through the mediating mechanism of knowledge management processes. Research limitations/implications: A key limitation is that the study is cross-sectional, and the findings may only be generalizable to developing countries context. Originality/value: Previous studies have focused on supervisor–employee relationship but not in the context of knowledge worker productivity. This article fulfills this gap through understanding the impact of abusive supervision on the knowledge worker productivity in relation to KM processes (knowledge creation, sharing and application) by drawing upon the theoretical underpinning of knowledge worker productivity.